Occurrence of Three Headed Sternocleidomastoid Muscle and a Common Thyro-Linguo-Facial Vein – A Case Report - Gayathri S Prabhu,; Satheesha B Nayak,; Prakashchandra Shetty,; Deepthinath Reghunathan,; Prasad AM, (Faculty of Medicine, UKM Medical Centre, 2015)
Variant anatomy of muscles and veins of the neck is of importance to plastic surgeons, radiologists and general surgeons. We report the variations of sternocleidomastoid muscle and veins of the neck in the present article. Right sternocleidomastoid muscle had three heads of origin. The third head took its origin from the clavicle just lateral to the usual clavicular head. All the three heads were about 4 inches long and united with each other at the level of thyroid cartilage. There was no external jugular vein on the right side. The retromandibular vein united with facial vein to form common facial vein. Common facial vein joined with superior thyroid and lingual veins to form a thyro-linguo-facial trunk one inch below the angle of mandible. This trunk was about 2 inches long and terminated into the internal jugular vein. Knowledge of this case could be useful while raising a sternocleidomastoid flap, dministering anesthesia to brachial plexus, neck surgeries and carotid endarterectomy.